Asāsāt-i sākhtār-i Ḥizb-i Dimukratik-i Khalq-i Afghānistān - Kāviyanī, Najm al-Dīn (Instītūt-i ʻUlūm-i Ijtimāʻī, Kumītah-i Markazī-i H.D. Kh. A., 1982)
On the activities of Hizb-i Dimūkrātik-ī Khalq, ruling party of Afghanistan; includes its manifesto.